Forest biodiversity vis-a-vis climate change: The Indian scenario - Shah, Irfan Ali; Arunachalam, A (Indian Farming, 2015)
There is increasing evidence that forests will be profoundly affected by climate change. Our large population depends on climate sensitive factors like forestry for livelihood and survival. There is a need for developing and implementing adaptation as well as mitigation strategies to reduce the vulnerabilities brought about by climate change. On the whole a deeper understanding of the national circumstances and clean development imperatives is sin quonon for a comprehensive treatment of climate change issues, concerns and opportunities vis-a-vis forest biodiversity.